A Pyrrole-Imidazole Polyamide Is Active against Enzalutamide-Resistant Prostate Cancer - Kurmis, Alexis A.; Yang, Fei; Welch, Timothy R.; Nickols, Nicholas G.; Dervan, Peter B. (Cancer research (Chicago, Ill.), 2017)
The LREX' prostate cancer model is resistant to the antiandrogen enzalutamide via activation of an alternative nuclear hormone receptor, glucocorticoid receptor (GR), which has similar DNA-binding specificity to the androgen receptor (AR). Small molecules that target DNA to interfere with protein–DNA interactions may retain activity against enzalutamide-resistant prostate cancers where ligand-binding domain antagonists are ineffective. We reported previously that a pyrrole-imidazole (Py-Im) polyamide designed to bind the consensus androgen response element half-site has antitumor activity against hormone-sensitive prostate cancer. In enzalutamide-resistant LREX' cells, Py-Im polyamide interfered with both AR- and GR-driven gene expression, whereas enzalutamide interfered with only that of AR. Genomic analyses indicated immediate interference with the AR transcriptional pathway. Long-term treatment with Py-Im polyamide demonstrated a global decrease in RNA levels consistent with inhibition of transcription. The polyamide was active against two enzalutamide-resistant xenografts with minimal toxicity. Overall, our results identify Py-Im polyamide as a promising therapeutic strategy in enzalutamide-resistant prostate cancer. Cancer Res; 77(9); 2207–12. ©2017 AACR.